Motivation and Knowledge Improvement Model on Mobile Massive Open Online Course for Knowledge Worker - Suepphong Chernbumroong (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The rapid changing of technological advancements is affecting the workers at all levels, which required them to reskill and upskill. Knowledge workers are finding it increasingly challenging to cope with these transformations. Meanwhile, many organizations have prepared the learning space that can improve their workforce. It is also included with training reform for the knowledge workers who are already involved in the workplace. Massive Open Online Courses (MOOC) take place as innovation e-learning platforms that allow knowledge workers to acquire the knowledge at their own pace and time. Although many companies have adopted this technology to reskill and upskill their staff, the completion rate in MOOC is low. The principle of this study is to increase the completion rate in MOOC, which focuses on improving the motivation and knowledge of knowledge workers. Our research framework proposes a “motivation and knowledge improvement model” for analyzing and designing the MOOC platform, which comprises three levels. The context is the first level where the overview of the organization context is analyzed; business process, instructor, subject, and particular knowledge area. The second level is the concept, which mainly focuses on mapping the curriculum from the instructor before identifying the knowledge dimension and cognitive process for each learning object. Furthermore, it also selects the suitable gamification element for improving learner’s motivation in a MOOC platform. Thirdly, the artifact level aims at presenting the analysis of the platform, learning material, and gamification feature design. In this state, different features are created and designed, which aim to support the learning behavior of knowledge workers in the MOOC platform. The MOOC platform is the outcome of the research framework that applied to 2 companies as our case study. The platform allows organizations to create and share their curriculum and learning object, which is related to their business process in their workplace. Meanwhile, knowledge workers are also able to acquire their knowledge and learn on the platform, which proposed in our study. Furthermore, we also present the result of the implementation of the MOOC platform in many companies to facilitate the knowledge workers to acquire the knowledge and complete all tasks on the platform.